RAPID COMMUNICATION: A haplotype information theory method reveals genes of evolutionary interest in European vs. Asian pigs. (5th June 2018) - Hudson, Nicholas J; Naval-Sánchez, Marina; Porto-Neto, Laercio; Pérez-Enciso, Miguel; Reverter, Antonio
Abstract: Asian and European wild boars were independently domesticated ca. 10, 000 yr ago. Since the 17th century, Chinese breeds have been imported to Europe to improve the genetics of European animals by introgression of favorable alleles, resulting in a complex mosaic of haplotypes. To interrogate the structure of these haplotypes further, we have run a new haplotype segregation analysis based on information theory, namely compression efficiency (CE ). We applied the approach to sequence data from individuals from each phylogeographic region ( n = 23 from Asia and Europe) including a number of major pig breeds. Our genome-wide CE is able to discriminate the breeds in a manner reflecting phylogeography. Furthermore, 24, 956 nonoverlapping sliding windows (each comprising 1, 000 consecutive SNP) were quantified for extent of haplotype sharing within and between Asia and Europe. The genome-wide distribution of extent of haplotype sharing was quite different between groups. Unlike European pigs, Asian pigs haplotype sharing approximates a normal distribution. In line with this, we found the European breeds possessed a number of genomic windows of dramatically higher haplotype sharing than the Asian breeds. Our CE analysis of sliding windows captures some of the genomic regions reported to contain signatures of selection in domestic pigs. Prominent among these regions, we highlight the role of a gene encoding the mitochondrial enzyme LACTB which has been associated with obesity, and the gene encoding MYOG a fundamental transcriptional regulator of myogenesis. The origin of these regions likely reflects either a population bottleneck in European animals, or selective targets on commercial phenotypes reducing allelic diversity in particular genes and/or regulatory regions.